2022
DOI: 10.3390/s22010349
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient 5G Data Plan Approach Based on Partially Distributed Mobility Architecture

Abstract: Reaching a flat network is the main target of future evolved packet core for the 5G mobile networks. The current 4th generation core network is centralized architecture, including Serving Gateway and Packet-data-network Gateway; both act as mobility and IP anchors. However, this architecture suffers from non-optimal routing and intolerable latency due to many control messages. To overcome these challenges, we propose a partially distributed architecture for 5th generation networks, such that the control plane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Our study indicated that the quality of US images transmitted from the telerobotic US system over the 5G network was comparable to that of conventional US system, fulfilling the diagnostic demand. The transmission speed (peak rate of up to 20 Gbps) of the latest 5G network is 1.5 times better than that of the current 4G network, and the delay (approximately 1-10 ms) is reduced by a factor of 10 [34]. The application of 5G telecommunication technology substantially increases the data transmission capacity and resolves the issues of latency, which allows long-distance original US image acquisition, transmission, analysis, and processing, with high-precision synchronisation of multiple audio-visual signals.…”
Section: Discussionmentioning
confidence: 91%
“…Our study indicated that the quality of US images transmitted from the telerobotic US system over the 5G network was comparable to that of conventional US system, fulfilling the diagnostic demand. The transmission speed (peak rate of up to 20 Gbps) of the latest 5G network is 1.5 times better than that of the current 4G network, and the delay (approximately 1-10 ms) is reduced by a factor of 10 [34]. The application of 5G telecommunication technology substantially increases the data transmission capacity and resolves the issues of latency, which allows long-distance original US image acquisition, transmission, analysis, and processing, with high-precision synchronisation of multiple audio-visual signals.…”
Section: Discussionmentioning
confidence: 91%
“…iv) Signaling overhead: with centralized solutions, network resources can be wasted with a lot of exchange of mobility-related signaling messages during handovers. With the routing-based DMM approach [22], the exchange of mobility-related signaling messages is optimized. A single network prefix (i.e., IP address) can be used by the MN while roaming a particular DMM domain.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, reducing the probing redundancy often means reducing the discovery of additional routes because of the load balancing phenomenon [ 32 ]. The distributed architecture [ 33 ] will help to improve the integrity and reliability of network topology discovery and can support router identification on the basis of this. How to introduce the approach into multi-source topology probing and strike a balance between reducing probing redundancy and discovering additional routes will be investigated in future work.…”
Section: Discussionmentioning
confidence: 99%